ChemInform Abstract: Phase‐Transfer Catalyzed Sulfenylation of 3‐Substituted‐2‐oxindoles. Issue 32 (22nd July 2016) - Itoh, Takashi; Nagata, Kazuhiro; Sano, Daisuke; Aoyama, Osamu; Kanemitsu, Takuya; Miyazaki, Michiko; Odanaka, Yuki; Machida, Ayano
Abstract: The asymmetric sulfenylation of oxindoles using a chiral phase‐transfer catalyst derived from Cinchona alkaloids affords a range of optically active 3‐sulfenyl‐2‐oxindoles.